Institutions promoting budgetary discipline: evidence from Swedish municipalities - Jens Dietrichson; Lina Maria Ellegård (Lund University, School of Economics and Management, Department of Economics, 2012)
Conflicts of interest within hierarchic government organizations regarding the importance of fiscal discipline create the need for institutions that curb the bargaining power of units in charge of implementing policy and align their incentives to the interests of the whole organization. We examine this general public sector problem by collecting unique data on budget institutions and conflicts of interest within the Swedish municipalities. Our estimations suggest that institutions pertaining to both the planning stage and the implementation stage of the budget process are important for fiscal performance. The fiscal surplus is higher in municipalities that have centralized their budget process to some degree, and where local committees are allowed to carry over surpluses or forced to carry over deficits between fiscal years. The associations however differ between municipalities with different degrees of conflicts of interests, calling for further research to understand the incentives given by the result carry-over rules. We further find that the fiscal surplus is higher in municipalities where local managers face a relatively high risk of dismissal as a consequence of budget deficits.
Keywords: D02; D73; H61; H62; H72; 330; budget institutions; public organizations; municipalities; deficit/surplus